Using numerical analysis of ordinary differential equation systems to predict the chemical concentration after plasma irradiation - T. Kladphet; V. P. Thai; W. T. L. S. Fernando; K. Takahashi; T. Kikuchi; T. Sasaki (AIP Advances, 2022)
In this study, a zero-dimensional numerical simulation of the atmospheric pressure plasma (APP) interface with a liquid solution was performed. By assuming that the solution reaction is dependent on the injection of radicals and electrons, we were able to obtain a single short APP discharge with the liquid solution. This study can predict excitation temperature, electron temperature, and population densities of species and result in optimum conditions for a chemical reaction for the synthesis of nanoparticles or other applications of the reaction between APP and liquid surface. This work aims to explain the effect of pH values on the synthesis of gold nanoparticles compared with experimental results. We found that the effect of pH value is expected to impact the generation of gold nanoparticles. Therefore, a high pH value is suitable for generating gold atoms for nano-synthesis. The fundamental plasma properties, such as population density, electron temperature, excitation temperature, and gas temperature, and chemical reaction process were studied. The simulation results were consistent with the experimental observations.